Exploring stress-induced cognitive impairment in middle aged, centrally obese adults. (January 2013) - Lasikiewicz, N.; Hendrickx, H.; Talbot, D.; Dye, L.
<x xml:space="preserve">Abstract</x> Extensive research has shown that psychosocial stress can induce cognitive impairment. However, few studies have explored impairment following acute stress exposure in individuals with central obesity. Central obesity co-occurs with glucocorticoid excess and can lead to elevated cortisol responses to stress. It is not clear whether centrally obese individuals exhibit greater cognitive impairment following acute stress. Cortisol responses to stress versus no-stress control were compared in 66 high- and low waist to hip ratio (WHR) middle-aged adults (mean age of 46 ± 7.17 years). Cognitive performance post exposure was assessed using Cambridge Automated Neuropsychological Test Battery. It was hypothesised that high WHR would exhibit greater cortisol in response to stress exposure and would show poorer cognitive performance. Males, particularly of high WHR, tended to secrete greater cortisol during stress exposure. Exposure to stress and increasing WHR were specifically associated with poorer performance on declarative memory tasks (spatial recognition memory and paired associates learning). These data tentatively suggest a reduction in cognitive performance in those with central obesity following exposure to acute stress. Further research is needed to elucidate the effects of stress on cognition in this population.